Expanded Disclosures and the Increased Usefulness of Earnings Announcements - Francis, Jennifer; Schipper, Katherine; Vincent, Linda (The Accounting Review, 2002)
We investigate three explanations for prior studies' finding that the usefulness of earnings announcements, as measured by their absolute market responses, has increased over time. We confirm this increase for a sample of 426 relatively large, stable firms over 1980–1999. We find no evidence that this over-time increase in the magnitude of the market reaction to our sample firms' earnings announcements is attributable to increases in the absolute amount of unexpected earnings conveyed in the announcements or to increases in the intensity of investors' average reaction to unexpected earnings. To test the third explanation—an over-time expansion in the amount of concurrent (with bottom line earnings) information in earnings announcement press releases—we analyze and code the contents of 2,190 earnings announcement press releases made by 30 of our sample firms over 1980–1999. Concurrent disclosures increased significantly over this period and we find that these concurrent disclosures, especially the inclusion of detailed income statements, explain increases in the absolute market reactions to earnings announcements for our sample firms.